A Critique of Liberal Theory of Justice in E. Frazer‘s and N. Lacey‘s Political Philosophy - Droblytė, Patricija (Problemos, 2004)
The article discusses E. Frazer and N. Lacey’s feminist project of the theory of justice. The project is being developed through a critique of formalist methodology, characteristic of Kantian liberal theories of justice, and is based on the idea of a methodological synthesis of social and political theory. The possibility of synthesis is revealed through a combination of interpretivist and ontological realist approaches to the issue of justice. Their main reproach to Kantian theories of justice is that they are ill-equipped to endogenize mechanisms of social exclusion and domination, operating in society, which fails to distribute justice so that it may serve a well-being of each individual person.